The role of tawheedic stimulus in the conscience of muslim individuals - Shuriye, Abdi Omar (MCSER-CEMAS-Sapienza University of Rome, 2014)
Muslim individual’s worldview, culture and ethics are based on tawheed. In social, political and religious contexts, emotional state and motivational status of these individuals also inject perceptional premise to the way these individuals set value related priorities. The way Muslims see things, are mainly derived from faith, experience and family background. Values, knowledge and religious consciousness are therefore, the essence of tawheed in the mind of modern Muslim individuals. The key objective of this paper is to assess how these values are perceived by Muslim individuals in relation to the current world affairs and human relation within the socio-political and diverse worldviews. Muslim normative epistemological attitude towards tawheedic ethos in relation to the current reality of the technological and scientific development must be reassessed for further contextualization. Islam advocates good reasoning and tawheed has to be comprehended within the cognitive apparatus of the modern Muslim individual.